Enhancing Social Literacy Through Interactive Digital Media in Secondary School Social Studies - Lailaitul Qodriyah; Siti Fadiyah (Journal of Smart Pedagogy and Education, 2025)
Indonesia currently faces a critical educational paradox characterized by high institutional access yet alarming deficits in functional literacy, particularly within Secondary Social Studies. This study investigates the utilization of interactive digital media to resolve this "literacy emergency" and enhance students' social competencies. Employing a systematic qualitative methodology grounded in the ADDIE model and Johnston’s Digital Engagement Theory, the research analyzes the integration of digital platforms with indigenous local wisdom. The findings demonstrate that transforming static instruction into immersive experiences using tools like Augmented Reality and interactive modules raises student engagement from a moderate 60% to a significant 93%. This pedagogical shift effectively bridges the disconnect between abstract curricular concepts and students’ sociocultural realities. Ultimately, the research concludes that culturally responsive digital environments are indispensable for fostering critical thinking and civic responsibility, thereby equipping the "digital native" generation with the necessary skills to navigate complex societal dynamics in the 21st century.